(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
As part of general scientific and technical progress, the constant introduction of new technologies makes them an integral part of a particular field of medicine. A modern trend in the development of surgery is to reduce the invasiveness and trauma of surgical interventions. In connection with the development of surgical technologies, one of the main tasks in surgery is to minimize surgical trauma and the subsequent reduction in the number of postoperative complications and mortality, as well as the duration of inpatient treatment of patients while maintaining the quality of surgical care. This goal in abdominal surgery canbe achieved with the wide and widespread introduction of endosurgical technologies into everyday practice.